Occultist in Islam and Christianity (Comparative Studies of the Qur'an and Bible) - Siswanto, Siswanto; Ulum, Miftahul; Wijayanti, Sherina; Sunarya, Adi; Wijaya, Roma (Qur'an and Hadith Academic Society, 2024)
This study examines the concept of occultism. Here, the author focuses on the two religions, Islam and Christianity, because both are the most followed religions in Indonesia, so they significantly impact the understanding of the Occult in society. Therefore, the formulation of the problem in this paper is the views of Islam and Christianity in understanding the Occult and the differences and similarities between Islam and Christianity in narrating the Occult in their holy books, both the Qur'an and the Bible. This research is qualitative, library research that accumulates documentation data. The comparative study used in this article aims to analyze the differences and similarities in the narratives of Islam and Christianity in understanding the Occult. The results of this study are: First, in the Qur'an, occult events occur in the event of the prophet Musa (Q.S. Al-A'raf: 109-120), where there is mention of the word magic, witch. In the Bible, the term occult is not explicitly found, but as in 1 Cor. 8:4-7 regarding the rejection of meat sacrificed to idols, for there is no God but God. Second, there is a difference between the terms in the Qur'an and the Bible about the Occult. The Qur'an mentions magic, while the Bible is another Allah that claims to understand an object or to bind himself to an angel. The similarities between Islam and Christianity both agree with the rejection of the Occult.